The Dedekind different for a uniform set of points in Pn - Tran, Nguyen Khanh Linh; Le, Ngoc Long (Hue University Journal of Science: Natural Science, 2022)
Given a set of s distinct points X in the projective space Pn over a field K, we are interested in studying the uniformity of X. Explicitly, we work out an algorithm for checking the uniformity of X and we apply the Dedekind different to characterize some uniformity conditions of X.